Primerjava triboloških lastnosti mineralnih in repičnih mazalnih olj - Arnšek, Aleš (Strojniški vestnik, 2001)
In the present work, physical and chemical properties of rapeseed-based oils before and after mechanical tests are presented. Physical and chemical properties are determined with the measurement of viscosity, acids formed during oil oxidation (neutralization number) and infrared spectrum analysis of tested oils. The results of testing the tribological characteristics of biodegradable repeceed-based hydraulic/transmission oils showed, that they exibit better or even similar mechanical properties, but worse oxidative stability compared with a corresponding mineral-based oil. The hydraulic/transmission rapeseed-based oils with their native properties and additives have similar lubrication properties as lubricants based on mineral oils, but they are in addition biodegradable and non-toxic.
Keywords: olja repična; viskoznost kinematična; število nevtralizacijsko (TAN); IR spektri; lastnosti maziv; maziva; repično olje; fizikalne lastnosti; kemijske lastnosti; mazanje